Dual-channel OCT for velocity measurement in microfluidic channels. - Rigas, Evangelos; Hallam, Jonathan M.; Ford, Helen D.; Charrett, Thomas O. H.; Tatam, Ralph P. (OSA, 2018)
A dual-beam Optical Coherence Tomography system has been developed, using a bespoke dual optical fibre, to simultaneously image microfluidic channel structures and measure high velocity flows (presently 250μm/s) from a single optical access point.